Comparative modeling of proteins: A method for engaging students' interest in bioinformatics tools. Issue 1 (25th October 2013) - Badotti, Fernanda; Barbosa, Alan Sales; Reis, André Luiz Martins; do Valle, Ítalo Faria; Ambrósio, Lara; Bitar, Mainá
<x xml:space="preserve">Abstract</x> The huge increase in data being produced in the genomic era has produced a need to incorporate computers into the research process. Sequence generation, its subsequent storage, interpretation, and analysis are now entirely computer‐dependent tasks. Universities from all over the world have been challenged to seek a way of encouraging students to incorporate computational and bioinformatics skills since undergraduation in order to understand biological processes. The aim of this article is to report the experience of awakening students' interest in bioinformatics tools during a course focused on comparative modeling of proteins. The authors start by giving a full description of the course environmental context and students' backgrounds. Then they detail each class and present a general overview of the protein modeling protocol. The positive and negative aspects of the course are also reported, and some of the results generated in class and in projects outside the classroom are discussed. In the last section of the article, general perspectives about the course from students' point of view are given. This work can serve as a guide for professors who teach subjects for which bioinformatics tools are useful and for universities that plan to incorporate bioinformatics into the curriculum. © 2013 by The International Union of Biochemistry and Molecular Biology, 42(1):68–78, 2014